2018
DOI: 10.1073/pnas.1712268115
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus integrity in old age is selectively related to memories linked with salient negative events

Abstract: SignificanceLocus coeruleus (LC) integrity in cognitively normal older adults is a potentially important preclinical marker in dementia. Our study establishes a link between variability in LC integrity and cognitive decline related to noradrenergic modulation in old age. We find that in older adults, reduced LC integrity explains lower memory performance. This effect was more pronounced for memory related to negative events, and accompanied by increased pupil diameter size in response to negative events. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
139
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 56 publications
15
139
1
Order By: Relevance
“…Animal and post-mortem human studies suggest a link between memory performance in aging and the integrity of the central noradrenergic system 7,10 . So far, in vivo research on humans, however, has been stymied by methodological difficulties in the reliable assessment of LC integrity 26,40,41 (but see Hämmerer and colleagues 11 ). Here, we took advantage of the paramagnetic properties of neuromelanin, a byproduct of NE synthesis, in T 1 -weighted MRI to image the LC in vivo 46,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and post-mortem human studies suggest a link between memory performance in aging and the integrity of the central noradrenergic system 7,10 . So far, in vivo research on humans, however, has been stymied by methodological difficulties in the reliable assessment of LC integrity 26,40,41 (but see Hämmerer and colleagues 11 ). Here, we took advantage of the paramagnetic properties of neuromelanin, a byproduct of NE synthesis, in T 1 -weighted MRI to image the LC in vivo 46,48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, direct in vivo evidence relating LC integrity to interindividual differences in general memory abilities is scarce. While there is an initial indication of a selective role of LC integrity, as indexed magnetic resonance imaging (MRI; see below), in the encoding of negative emotional events 11 , the relation of LC integrity to memory performance in general is still an open question. Given LC's pivotal role in age-related memory disorders like Alzheimer's disease 8,9,12 , this relationship, however, is of high clinical and scientific importance.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromelanin‐sensitive magnetic resonance imaging (NM‐MRI) can detect NM, a by‐product of noradrenaline metabolism, in the LC in vivo . Using NM‐MRI, recent studies have reported that LC integrity in old age is selectively related to memory and that LC signal intensity is associated with verbal intelligence in older adults . The neuromelanin of LC is significantly lower in MCI and Alzheimer's disease (AD) patients, compared with healthy controls .…”
mentioning
confidence: 99%
“…The contrast to noise ratio (CNR) estimated from in vivo imaging has been widely used as a marker of LC structural integrity for disease stratification, differential diagnosis (Ohtsuka et al, 2013, Takahashi et al, 2015, Ohtsuka et al, 2014, Matsuura et al, 2013), or to explain variance in cognitive performance (Clewett et al, 2018, Dahl et al, 2019, Hammerer et al, 2018). Previous 3T imaging studies typically employed 2D sequences with large slice thickness to improve the signal-to-noise ratio (SNR) and reduce the scan duration.…”
Section: Introductionmentioning
confidence: 99%
“…The application of LC CNR as an imaging biomarker in clinical studies relies on an adequate and unbiased estimation of the signal in disease groups where the neuronal loss relates to volumetric reduction (Theofilas et al, 2017). Manual segmentation is often used for extracting the LC signal, but this method relies on subjective estimations that only have fair to good intra-rater reliability (Tona et al, 2017, Hammerer et al, 2018). The manual segmentation approach becomes more unreliable when the signal-to-noise is reduced by pathological changes and when the signal is more dispersed by anisotropic resolution.…”
Section: Introductionmentioning
confidence: 99%